SOFTWARE PRODUCT LINE ENGINEERING. - Sugumaran, Vijayan; Park, Sooyong; Kang, Kyo C. (Communications of the ACM, 2006)
The article discusses the effects of globalization on software product line engineering. The software product line (SPL) is one of the most promising paradigms for increasing the productivity of information technology-related industries, since it allows them to both handle the diversity of the global market and reduce the time to market. SPL can be useful in improving the software development process by allowing companies to reuse assets from other products, which cuts costs and gives the user a more cohesive experience.